Pendampingan Penyusunan Laporan Keuangan Sederhana Bagi UMKM Kopi di Desa Kaongke-ongkea, Kecamatan Pasarwajo, Kabupaten Buton - Herman Herman; Muarif Leo; Winda Ayu Virginia; Irmawati Alimuddin; Resfika Aswira; Nurdin Nurdin (Abdimas Universal, 2022)
Buton Regency has potential in developing commodities, especially coffee, which is located in the village of Kaongke-ongkea, Pasarwajo District and is the first coffee village in Buton land. The problem faced by coffee UMKM entrepreneurs is that they do not yet know how to compile financial reports in a simple way, therefore the purpose of this service is to provide knowledge and understanding so that coffee UMKM entrepreneurs in Kaongke-ongkea Village can be independent, especially in recording and compiling financial reports in a timely manner. simple. This community activity program uses mentoring and training methods in the form of simple examples of transactions related to business in the coffee sector. With this service program, coffee UMKM entrepreneurs in Kaongke-Ongkea Village are expected to improve their understanding, knowledge and skills and be independent in compiling simple financial reports.